FLC design for multi-objective systems - Lim, Taeseung; Bien, Zeungnam (Zielona Góra: Uniwersytet Zielonogórski)
For a system with multiple objectives, designing the rule base for a fuzzy-logic controller (FLC) is not an easy task. In particular, when the fuzzy if-then rules are obtained from human operators, they can be inconsistent due to possibly conflicting multiple objectives. In this paper, we propose an FLC design scheme that is suitable for this type of systems.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka